Seasonally resolved diatom δ18O records from the west Antarctic Peninsula over the last deglaciation - Swann, George E.A.; Pike, Jennifer; Snelling, Andrea M.; Leng, Melanie J.; Williams, Maria C. (Elsevier, 2013)
Understanding the response of the Antarctic ice sheets during the rapid climatic change that accompanied the last deglaciation has implications for establishing the susceptibility of these regions to future 21st Century warming. A unique diatom δ18O record derived from a high-resolution deglacial seasonally laminated core section off the west Antarctic Peninsula (WAP) is presented here. By extracting and analysing single species samples from individual laminae, season-specific isotope records were separately generated to show changes in glacial discharge to the coastal margin during spring and summer months. As well as documenting significant intra-annual seasonal variability during the deglaciation, with increased discharge occurring in summer relative to spring, further intra-seasonal variations are apparent between individual taxa linked to the environment that individual diatom species live in. Whilst deglacial δ18O are typically lower than those for the Holocene, indicating glacial discharge to the core site peaked at this time, inter-annual and inter-seasonal alternations in excess of 3‰ suggest significant variability in the magnitude of these inputs. These deglacial variations in glacial discharge are considerably greater than those seen in the modern day water column and would have altered both the supply of oceanic warmth to the WAP as well as regional marine/atmospheric interactions. In constraining changes in glacial discharge over the last deglaciation, the records provide a future framework for investigating links between annually resolved records of glacial dynamics and ocean/climate variability along the WAP.